Effect of Rumen Modifier on Methanogenesis and Feed Digestibility under in Vitro Conditions - Lakhani, Neeti; Kamra, Devki Nandan; Lakhani, Preeti; Kala, Anju (Indian Journal of Animal Nutrition, 2019)
A rumen modifier which is a mixture of RM-7 [neem seed cake (Azadirachta indica), mahua seed cake (Madhuca longifolia), fennel seed (Foeniculum vulgare), harad (Terminalia chebula), fruit pulp of bahera (Terminalia bellirica), fruit pulp of amla (Phyllanthus emblica) and ajwain seed (Trachyspermum ammi) mixed in 2:2:2:1:1:1:1 proportion] was tested at 0 (control), 5, 10, 15 and 20% of the substrate along with 0.06% of sodium sulphate (except control) for their effects on in vitro methane production and feed fermentation. Inclusion of RM-7 at 5, 10, 15 and 20% of substrate along with 0.06% of sodium sulphate did not affect gas production but there was significant (p <0.01) reduction (18.5 and 34.1 per cent) in methane production as well as feed digestibility (60.88 to 52.71 per cent). Total volatile fatty acids were not affected by any of the treatments. There was no significant difference in the level of acetate, propionate, butyrate as well as acetate:propionate ratio. Ammonia nitrogen also showed no significant change on inclusion of rumen modifier. The results indicated that inclusion of rumen modifier (RM-7 at 5, 10, 15 and 20 per cent + 0.06 per cent sodium sulphate) did not affect total gas production but there was significant reduction in methane production with increasing levels upto 10 per cent.